Strategi Guru Pendidikan Agama Islam dalam Membangun Kedekatan Emosional Siswa melalui Pendekatan Love-Based Curriculum - Mochammad Yasin Yusuf; Zuhri Fahruddin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Emotional cohesion between teachers and students is an important factor in creating effective learning and supporting students’ character development in madrasahs. However, studies on the strategies used by Islamic Religious Education (PAI) teachers to build emotional relationships at the madrasah ibtidaiyah level remain limited. This study aims to analyze the forms of emotional closeness between teachers and students, the strategies employed by PAI teachers in fostering these relationships, and their impact on student development at MI Nurul Islam Yosowilangun Kidul. This research employed a qualitative approach with a descriptive method. Data were collected through two months of observation and interviews with PAI teachers, the principal, and the vice principal. Data analysis was conducted using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing, which were verified through source and technique triangulation. The findings revealed that emotional closeness was formed through daily interactions and shared religious activities. The main strategy implemented was the Affection-Based Curriculum, which contributed to improved discipline, religiosity, emotional stability, and public trust in the madrasah